A Critical Discourse Analysis of Gender Disparity in Taskmaster - Nauka Nayana Prasadini (English Language Education Study Program of STKIP PGRI Banjarmasin, 2021)
British comedy panel show is the television comedy genre that is known for spontaneous banters and humour. Despite the popularity, the shows in this genre are often criticized as